Effects of Sodium Selenite and Vitamin E on the Development of Morphine Dependency in Mice - Bohloul Habibi-Asl; Alireza Parvizpur; Kiarash Fekri; Hadis Jahanpanah; Hadis Rezaei; Mohammad Charkhpour (Tabriz University of Medical Sciences, 2021)
Background: Antioxidant drugs may be useful in preventing morphine-induced dependency bysuppressing oxidative stress. Vitamin E which has many essential roles in the body is a powerfulantioxidant. On the other hand, selenium is an essential trace element that plays a strong rolein various biochemical pathways. The aim of this study was to investigate the effects of sodiumselenite and vitamin E on morphine-induced dependency in mice. Methods: Ninety male mice, weighing 20 to 30 g, were randomly divided into 10 groups and weretreated as follows: a) saline and b) morphine groups were pretreated (for 2 days) with normalsaline (10 ml.kg-1.day-1, ip) then daily doses of normal saline (10 ml.kg-1.day-1, ip) and morphine(50 mg.kg-1.day-1) were added to the injections for the following 4 days, respectively. c, d, e)sodium selenite, f, g, h) vitamin E, i) vitamin E solvent (almond oil) and j) co-administrationgroups were pretreated (for 2 days) with sodium selenite (0.25, 0.5, 1 mg.kg-1.day-1, ip), vitaminE (20, 40, 60 IU.kg-1.day-1, ip), vitamin E solvent (10 ml.kg-1.day-1, ip) and combination of thedrugs respectively, then morphine doses (50 mg.kg-1.day-1, ip) were added to the injections forthe following 4 days. Withdrawal symptoms were evaluated after injecting naloxone (4 mg/kg/day). Biochemical evaluations were also performed. Results: The results showed that co-administration of sodium selenite and vitamin E (at lowdoses) significantly reduced morphine dependency (p < 0.05). Conclusion: The synergistic effect of sodium selenite and vitamin E can be a suitable andefficient approach to reduce dependency.